RANCANG BANGUN SISTEM MONITORING KUALITAS UDARA BERBASIS ANDROID - Pradana, Ronaldo Baja; Arnomo, Sasa Ani (LPPM Universitas Putera Batam, 2023)
In this era of rapid technological development, it is a crucial period where technology has become an inseparable part of everyday life. The significant increase in human activity has triggered various air pollution problems, including burning, waste, industrial waste, vehicle fumes, industrial fumes, and the use of electronic equipment, among others. Additionally, besides the aforementioned problem of air pollution, its impact can also lead to a variety of serious problems and the occurrence of health issues such as asthma, ISPA, lung cancer, and so on. Therefore, an Android-based application was created that can provide information about the current air quality in the user's area. This application can be used to monitor air quality in specific areas based on measurements and data collection. The method used for this research is the RAD (Rapid Application Development) method, which is suitable for developing software in a short time. We have also added a real-time air quality monitoring feature that can monitor air levels to determine if they are within normal levels or not. This allows users to combat air pollution and carry out continuous monitoring without being limited by space and time.